Educational Tourism Needs for Family Tourist Segment In Nakhonnayok Province - Srithong, Saranya; Kieanwatana, Komsit; Jamnongchob, Angsumalin; Saowapawong , Kingkanok (Academic Journal of Thailand National Sports University, 2018)
The purposes of this research were to survey tourist attractions and to study tourists’ needs for educational tourism in Nakhonnayok province.The samples were 400 Thai people whotraveled around attractions in Nakhonnayok province and 12 stake holders. A questionnaire and an Interview form were used as survey tools. The questionnaire was validated by five experts the result of index of item objective congruence (IOC), the lowest and highest was between .8 to 1 and the reliability of Cronbach’s Alpha Coefficient was .882 data were analyzed statistic using the percentage, means and standard deviation. Results were found that Nakhonnayok province has several educational tourism resources that can fulfill family tourist segment’s need. Respondents mainly had high educational tourism needs in accessibility ( = 3.19), attraction ( = 3.11), and amenities ( = 3.06).The guidelines for tourism and educational tourism rout development for family tourist segment should be initiate public and private sectors, local entrepreneur, and communities to cooperate for the sustainable tourism development.T here should be promoting educational tourist attractions for recognition, supporting educational tourism activities which have participation between tourist, attractions’ owners and communities, designing of tourism interpretations which suited for all family members, providing tourism facilities for elderly people, providing and ensuring tourists’ safety and security on the journey.